Meningkatkan Kompetensi Komunikasi Bahasa Arab dalamPembelajaran NahwuMelalui Pendekatan Komunikatif pada Mahasiswa Jurusan Pendidikan Bahasa Arab Fakultas Tarbiyah Keguruan UIN Suska Riau - Mainizar Mainizar (Sosial Budaya, 2011)
This research backgrounded by its low Arabic majors College Student ability class II. b deep get communications with Arabic good while is at in as well as outside class. Eventually their a large part indigenous pesantren's cabin. Learning winks Nahwu's college as bahagian (furu) of Arabic study must it gets to increase College Student ability in one's line learning which is gets communication word of mouth and also writing. To the effect research is subject to be see and figuring if Nahwu's learning with communicative approaching gets to increase College Student communication interest in Arabic? To reach to the effect upon was gathered data of semester College Student II. b, sitter lecturer, collaborator lecturer, meanwhile data collecting tech is done with essays oral, observation, questionnaire and discussion. Its result points out that Nahwu's learning with communicative approaching gets to increase College Student Arabic communication of point 67,66 as 70,76. Meanwhile Arabic communication interest Arabic majors College Student individually lies deep good category with appreciative range 70 onto, worked up of 42,31% as 73,15%. It means specified target as indicator of performance can be reached. Therefore Nahwu's learning with this approaching constitute strategy in point in increase College Student Arabic communication